2000
DOI: 10.1088/0031-9155/45/5/312
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral imaging approach in the diagnosis of cutaneous melanoma: potentiality and limits

Abstract: In an attempt to overcome the subjectiveness of clinical observation in the diagnosis of cutaneous melanoma, a computerized method is proposed. Reflectance images of 237 pigmented lesions (67 melanomas and 170 non-melanomas) were analysed using a telespectrophotometric technique. This device consists of a CCD camera with 17 interference filters. Images were acquired at selected wavelengths, from 420 to 1040 nm. Morphological and reflectance related parameters were extracted from the wavelength-dependent images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…A clinical study by an Australian group found that the biopsy ratios for general practitioners ranged from 82:1 for young patients to 10:1 for older patients. The biopsy ratio appears to be substantially reduced with the use of newer technologies such as dermoscopy, surface microscopy, and multispectral imaging (28,(30)(31)(32)(33)(34)(35)(36)(37)(38). Westerhoff and colleagues found that the accuracy of melanoma diagnosis could be improved from 63% to 76% with the aid of surface microscopy (30).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study by an Australian group found that the biopsy ratios for general practitioners ranged from 82:1 for young patients to 10:1 for older patients. The biopsy ratio appears to be substantially reduced with the use of newer technologies such as dermoscopy, surface microscopy, and multispectral imaging (28,(30)(31)(32)(33)(34)(35)(36)(37)(38). Westerhoff and colleagues found that the accuracy of melanoma diagnosis could be improved from 63% to 76% with the aid of surface microscopy (30).…”
Section: Discussionmentioning
confidence: 99%
“…More recently wavelength-dependent reflectance images of skin have been obtained. 57 Both light that entered the tissue and was scattered back to the surface as well as reflection off the tissue surface were measured, making interpretation of the multispectral images difficult. A recent study by V.P.…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…[9][10][11][12] Images using various spectral bands from 420 to 1040 nm to enhance the ABCD criteria has been shown to improve the accuracy of detecting melanoma. [13][14][15] In our series for this purpose 47 pigmented lesions of thirty-nine patients were evaluated.…”
Section: Discussionmentioning
confidence: 99%